Full-duplex mmWave MIMO with finite-resolution phase shifters - R. López-Valcarce; M. Martínez-Cotelo (IEEE Trans. Wireless Communications, 2022)
Enabling simultaneous transmission and reception on the same carrier frequency, i.e., full-duplex (FD) communication, critically requires that the self-interference (SI) be sufficiently suppressed. We investigate the design of precoders and combiners for an FD millimeter wave point-to-point bidirectional link, where dense antenna arrays provide an opportunity for SI suppression via beamforming cancellation. In practice the precoders and combiners are usually implemented in a hybrid digital/analog fashion with a reduced number of radio frequency (RF) chains, and it becomes necessary to overcome a number of limitations imposed by this structure. We focus on a hybrid architecture with a phase shifter-based fully-connected analog stage, assuming finite-resolution phase shifters. To avoid analog-to-digital converter saturation at the receiver, the proposed design aims at cancelling SI at the analog combiner output. Although accurate SI suppression is difficult with low-resolution phase shifters, our design is able to provide reasonable performance, significantly improving upon previous approaches, and allowing to efficiently exploit the availability of RF chains to partially compensate for coarse phase quantization effects.
Keywords: full-duplex; mmWave; rodin